El perfil del administrador mexicano y su potencial de internacionalización (The Mexican manager’s profile and his international potential) - Guerra, P. (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Resumen. El objetivo principal de esta investigación es mostrar las características del administrador mexicano, especialmente el que dirige y toma decisiones en las Pequeñas y Medianas Empresas, y determinar que tantas posibilidades tiene para internacionalizar sus operaciones, y de esta forma insertar su empresa dentro del nuevo orden mundial, que exigen la internacionalización, como un requisito básico de supervivencia. La razón por la cual fue seleccionado el administrador de las Pequeñas y Medianas Empresas (que en adelante se denominará en forma breve como PYMES), es debido a que como se mostrará mas adelante, es la categoría de empresas con mayor población en México. Así mismo, este documento trata de mostrar cuales serian las recomendaciones que después de una investigación de campo y documental, serian adecuadas para los empresarios mexicanos, para lograr el objetivo de la internacionalización de sus operaciones. Abstract. The development of this research leads us towards the expert’s opinion of businessmen and people involved in the international business processes. At the early stages of the research, we identified the urgency of the matter that the Mexican executives must be prepared to respond in a competitive fashion to the global market, and also we found out that there is a trend in which it is necessary to adopt a series of characteristics or profiles that are in line with export/ import activities. This will facilitate and certainly improve the ideal profile of Mexican entrepreneurs, whereby our executives could manage independently in all walks of professional lines of businesses at world wide scale. This preparation precludes the extinction of the Mexican entrepreneurs from general competition and hence will allow their survival in the market economy. Abstract. The development of this research leads us towards the expert’s opinion of businessmen and people involved in the international business processes. At the early stages of the research, we identified the urgency of the matter that the Mexican executives must be prepared to respond in a competitive fashion to the global market, and also we found out that there is a trend in which it is necessary to adopt a series of characteristics or profiles that are in line with export/ import activities. This will facilitate and certainly improve the ideal profile of Mexican entrepreneurs, whereby our executives could manage independently in all walks of professional lines of businesses at world wide scale. This preparation precludes the extinction of the Mexican entrepreneurs from general competition and hence will allow their survival in the market economy.